Another Look at Kant and Degrees of Responsibility - Frierson, Patrick (Con-Textos Kantianos. International Journal of Philosophy, 2018)
In “Kant and Degrees of Responsibility,” Joe Saunders claims that “Degrees of responsibility are important for both our moral and legal practices” (p. 1) and argues that “transcendental idealism precludes Kant from vindicating these judgments [about degrees of responsibility]” (p. 11); thus, we have reasons to reject Kant’s transcendental idealism. In this paper, I show how Kant’s transcendental idealism can accommodate and provide a metaphysical account for degrees of responsibility. Whether this “vindicates” such judgments depends upon how much one expects a philosophical account to do; I defend modesty there while admitting a reasonable desire for reflection on how we can and should make such judgments. Finally, I raise the question of just how important judgments of moral responsibility are. Rather than looking to metaphysics to figure out how to vindicate judgments about degrees of responsibility, I suggest we look to the practical purposes such judgments serve.